Reasons for poor or borderline cataract surgical outcomes at Nkhoma hospital in Malawi: a retrospective analysis - Chingwengwe, Martha (Division of General Surgery, 2025)
Cataract is the main cause of blindness worldwide. Cataract surgery is the most effective intervention for cataract blindness. However, poor or borderline outcomes following cataract surgery reduces the effectiveness of this strategy to eliminate this cause of avoidable blindness. This study aimed to determine the reasons for poor or borderline cataract surgical outcomes in people who had undergone cataract surgery. This was a retrospective analysis of theatre records of people who had undergone cataract surgery at Nkhoma Hospital between January and December 2019. All people that recorded a post-operative visual acuity of 6/18 and worse in either or both eyes were included in the study. Data was collected on variables concerning demographics, aspects of referral, preoperative examination, intraoperative findings and post- operative examination. The study determined that 52.2% of poor or borderline cataract surgical outcomes at Nkhoma Hospital were because of ocular comorbidity known to cause vision loss and other comorbidity likely to affect vision adversely, 25.8% because of uncorrected refractive error (post-operative visual acuity with pinhole improved to 6/18 or better) and 3.7% because of intra-operative complications. For a total of 13.5% of the poor and borderline surgery outcome cases, no reasons could be determined with the data available. The study revealed that the reasons for poor or borderline surgery outcome at Nkhoma Hospital are complex and are influenced by decision-making about whether to perform the surgery, regardless of pre-operative visual acuity findings, presence of co-morbidities or the reasonable expectation to deliver an improved outcome following surgery. This emphasizes the need for improved knowledge and skills about referrals, pre-operative screening, post-operative follow-up and allocation of workloads to members of the entire cataract surgical service team.